Assessing and enhancing EN 16883:2017. Issue 1 (October 2021) - Leijonhufvud, G L; Buda, A; Broström, T
Abstract: This paper describes the work undertaken within the international project IEA SHC Task 59 Renovating Historic Buildings Towards Zero Energy to produce a handbook for the planning of energy retrofits in historic buildings. The handbook is an attempt to increase use and usability of the European standard EN 16883:2017 - Conservation of cultural heritage -Guidelines for improving the energy performance of historic buildings. The standard provides a decision roadmap for how energy efficiency measures can be identified that both respect the heritage values of the building and improves the energy performance. It also provides general information about energy efficiency in historic buildings. There has been a lot of interest in this standard from researchers in the field of energy efficiency in historic buildings, but it has not been widely used in practice. The first part of the paper summarises an assessment of the use, or lack thereof, of the standard. The assessment is based on nine European case studies that identify how the European standard can be complemented with additional resources, examples and guidance. In the second part the work with a handbook complementing the standard is outlined, and recommendations to future revisions of the standard are suggested.